Pemberdayaan Keluarga terhadap Peran Keluarga dalam Pencegahan Anemia pada Ibu Hamil - Noviyanti, Merry; Triharini, Mira; Ulfiana, Elida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to provide opportunities for pregnant women and their families to receive education and information regarding the role of the family in preventing anemia in pregnant women. The method used to search for articles relevant to the study in February – March 2024 was carried out using three stages: planning, conducting, and reporting. The results show that 10 international articles analyzed in this paper have passed screening according to the inclusion and exclusion criteria. The journals or articles reviewed include the year of publication, database, research design, and location. In conclusion, the family's role is very important in ensuring the health of the mother and future baby. The family is a support system that is very close to pregnant women so that it can motivate and provide support in preventing anemia. Keywords: Anemia Prevention, Family Empowerment, Family Role, Health Belief Model